K-12, college/university, and mass shootings: similarities and differences. Issue 6 (2nd November 2021) - Kowalski, Robin Marie; Leary, Mark; Hendley, Tyler; Rubley, Kaitlyn; Chapman, Catherine; Chitty, Hannah; Carroll, Hailey; Cook, Andrew; Richardson, Emily; Robbins, Chelsea; Wells, Stephen; Bourque, Leah; et al.
ABSTRACT: In a 2003 study, we examined five antecedents of school shootings – a history of rejection, acute rejection experience, history of psychological problems, fascination with death or violence, and fascination with guns. In three studies, the current project examined the role of these factors in 57 K-12 shootings, 24 college/university shootings, and 77 mass shootings that occurred since the original study. Over half of all shooters had a history of psychological problems. More K-12 shooters than college or mass shooters displayed a history of rejection. However, more mass than school shooters had experienced an acute rejection, such as a workplace firing. The characteristics identified in the original study appeared as common antecedent conditions of not only K-12 shootings but college/university and mass shootings as well. These results identify problems that can be addressed to minimize the occurrence of school and mass shootings.